Potent inhibitory effect of silibinin from milk thistle on skin inflammation stimuli by 12-O-tetradecanoylphorbol-13-acetate. Issue 12 (8th September 2015) - Liu, Wenfeng; Li, Yonglian; Zheng, Xi; Zhang, Kun; Du, Zhiyun
Abstract : Silibinin, a major polyphenol in milk thistle, has been reported to have multiple pharmacological activities; therefore, there is an urgent need to well understand how silibinin works on inflammation-associated skin diseases. Abstract : Silibinin, a major polyphenol in milk thistle, has been reported to have multiple pharmacological activities; therefore, there is an urgent need to well understand how silibinin works on inflammation-associated skin diseases. We herein designed silibinin on 12- O -tetradecanoylphorbol-13-acetate (TPA)-stimulated skin inflammation to test its inhibitory effects. It was demonstrated that silibinin, applied topically onto mouse ears following TPA stimulation, effectively down-regulated the expressions of TPA-induced interleukin-1β (IL-1β), interleukin-6 (IL-6), necrosis factor-alpha (TNF-α) and cyclooxygenase-2 (COX-2) in a dose-dependent manner. Further mechanistic investigations indicated that silibinin suppressed the expression of IκB kinase (IKK) by inhibiting the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) signaling pathway, and thereby suppressing TPA-stimulated nuclear factor-κB (NF-κB) activation. Promisingly, silibinin, used for transdermal application, may be a potent naturally occuring anti-inflammatory agent for the prevention of inflammation-associated skin diseases.